LEGITIMATE EXPECTATIONS AS AN ELEMENT OF THE FAIR AND EQUITABLE STANDARD OF TREATMENT OF FOREIGN INVESTMENTS IN ARBITRAL PRACTICE - Đundić, Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Fair and equitable standard of treatment of foreign investments represents an integral part of all modern international agreements on protection and encouragement of foreign investments. The key element of its contents, according to arbitral practice, is an obligation of the host state to provide the investor with the treatment in accordance with basic expectations that he or she had at the time of the investment with regard to economical and legal conditions in the host state. The paper analyzes the most important awards of arbitral tribunals dealing with legitimate expectations of the investor as a part of the fair and equitable treatment standard. A considerable attention is dedicated to identifying the behavior of the host state capable of creating legitimate expectation which enjoy legal protection as well as to detecting the requirements for the development of reasonable expectations.